Effect of processing parameters on recovery of hot process virgin coconut oil and co-products utilization - Manikantan, M.R.; Arivalagan, M.; Mathew, A.C.; Hebbar, K.B. (Journal of Plantation Crops, 2015)
Virgin coconut oil (VCO) is growing in popularity as functional food, cosmetic and pharmaceutical oil. The high cost of VCO is due to its low recovery. In order to improve the recovery, the effect of milk expelling methods (manual and mechanical) and pre- treatments (slicing, pulverizing and blanching) on coconut milk and hot process VCO recovery with respect to fresh coconut kernel weight was studied. The blanching and pulverizing yielded more milk and VCO recovery in both manual and mechanical expelling methods. The recovery of coconut milk and VCO ranged from 34.0 to 51.6 per cent and 14.2 to 22.4 per cent respectively. Among the different treatment combinations, pulverized, blanched and double screw pressed coconut kernel yielded the highest milk and VCO recovery. The per cent recovery of two important co-products namely coconut milk residue and VCO cake ranged from 38.5 to 55.6 and 6.3 to 8.8 respectively. An attempt was made to recover the oil from 8 per cent dried coconut milk residue and VCO cake in commercial oil expeller. The oil recovery from milk residue and VCO cake flour was 41.2±1.1 per cent and 25.8±1.0 per cent respectively. The dried coconut milk residue and VCO cake flour was utilized in the preparation of extrudates and sweet snacks along with the broken rice, maize grits and pearl millet grits.